Community-Based Karawitan Education and Cultural Sustainability: The Rosa Mustika Laras Community at Saint John the Evangelist Catholic Church, Kudus - Nugraha, Laurensius Kharisma Adi; Sejati, Irfanda Rizki Harmono (Jurnal Ragam Pengabdian, 2026)
The sustainability of Javanese karawitan is increasingly challenged by cultural transformation and declining youth participation. While previous studies have examined karawitan in educational settings, limited attention has been given to its development within religious communities as a model of arts education and cultural preservation. This study investigates community-based karawitan education implemented by Rosa Mustika Laras at Saint John the Evangelist Catholic Church in Kudus, Central Java. A qualitative case study was employed using participant observation, semi-structured interviews, and document analysis. Data were analyzed through an interactive model, with credibility ensured by triangulation and member checking. The findings reveal that Rosa Mustika Laras integrates musical instruction, cultural transmission, and liturgical inculturation through regular ensemble practice and intergenerational learning. Beyond supporting Catholic liturgy, the community actively promotes cultural sustainability through public performances, educational outreach, and institutional collaboration. These activities strengthen cultural identity, encourage community participation, and support the regeneration of karawitan practitioners. This study demonstrates that religious communities can serve as effective spaces for community-based arts education while functioning as agents of intangible cultural heritage preservation.